The role of juvenile hormone and insulin/TOR signaling in the growth of Manduca sexta - Hatem, Nicole E. (2015)
In many insect species, fitness trade-offs exist between maximizing body size and developmental speed. Understanding how various species evolve different life history strategies requires knowledge of the physiological mechanisms underlying the regulation of body size and developmental timing. Here the roles of juvenile hormone (JH) and insulin/target of rapamycin (TOR) signaling in the regulation of the final body size were examined in the tobacco hornworm, Manduca sexta.